PREVALENCE AND CHARACTERIZATION OF SEXISM IN THE SPANISH CONTEXT (Revista Contexto & Educação, 2022)
Sexism is defined as a discriminatory attitude directed towards people by virtue of their  belonging to a certain biological sex, and, therefore, sexist attitudes constitute the main axis on  which the relations of inequality between men and women are maintained. Thus, it is important  to keep in mind that, although in western countries sexism manifests itself in a subtler way,  recent researches corroborate that citizens continue to have sexist beliefs. Therefore, we  propose to identify the sexist attitudes of a sample of 692 participants (71.1% women, 28.9%  men) between 18 and 70 years old, and to explore the sociodemographic variables associated  with a more sexist profile. For this, the Inventory of Ambivalent Sexism was administered,  which evaluates both hostile sexism and benevolent sexism. The results reveal that 26.9% of  the sample shows sexist attitudes, with benevolent sexism being more common (34.8%). People  with this type of attitude are, to a greater extent, men (t = 8.82, p
Keywords: Sexist attitudes; Hostile sexism; Benevolent sexism; Sociodemographic profile